Racialization of African Migrants in Transit Through Costa Rica - Navarro Alvarado, Guillermo A. (2024)
The transit of African migrants through Costa Rica has increased since the early 2000s, implying institutional and community transformations for the country and the communities that receive them. This article analyzes the forms of racialization and rejection of these groups of people, as well as the institutionalization of these social practices in migration management policies, based on qualitative fieldwork conducted between 2021-2022. This research concludes that the memories and social interactions between communities and African migrants were structured on malleable dynamics of racialization, which configured dynamics of rejection, hospitality and forms of institutionalization, these were expressed in forms of racialization based on the alleged smell, skin color and cultural differences.